Trust and Psychosomatic Complaints in Adolescence: Findings From a Swedish Cohort Study - Sara Brolin Låftman; Viveca Östberg; Jonas Raninen; Jonas Raninen (Frontiers Media S.A., 2023)
Objectives: To examine the cross-sectional and longitudinal associations between generalised and institutional trust and psychosomatic complaints in mid and late adolescence.Methods: Data were derived from the Swedish cohort study Futura01, using survey information collected amongst 3,691 grade 9 students (∼15-16 years, t1) who were followed-up 2 years later (∼17-18 years, t2). Registry information on sociodemographic characteristics was linked to the data. Linear regression analyses were performed. The longitudinal analyses applied the first difference (FD) approach as well as the lagged dependent variable (LDV) approach. Covariates included gender, family type, parental education, parental country of birth, and upper secondary programme.Results: Higher levels of generalised and institutional trust were cross-sectionally associated with lower levels of psychosomatic complaints at both time points. The FD analyses showed that increases in generalised and in institutional trust between ages 15-16 and 17-18 years were associated with corresponding decreases in psychosomatic complaints. The LDV analyses demonstrated reciprocal temporal associations between trust and psychosomatic complaints.Conclusion: The findings indicate that trust is a social determinant of psychosomatic complaints in adolescents, but also that health may affect trust.